„Dr. Vojtěch Měrka is on Immediate Leave from which he will not Return“: to the Fate of Czech Professor in Slovakia 1919 – 1938 / „Dr. Vojtěch Měrka odchádza na okamžitú dovolenku, z ktorej sa nevráti”: K osudom českého profesora na Slovensku 1919 – 1938 - MIKULÁŠOVÁ, Alena (Studia Historica Nitriensia)
After the First World War, several thousand teachers from Czech countries worked in Slovakia. They came or were assigned to Slovakia to supplement the missing teaching capacities. The paper focuses on personality, activities and work of Vojtěch Měrka in period 1919 – 1938 while he was active as professor and later school director in towns Košice and Nitra. In addition to teaching, he was active in various fields and cultural sphere. After the declaration of Slovakia’s autonomy (October 6, 1938), Hlinka´s Slovak Peoples Party became a key political force in Slovakia. Its representatives had the ambition to eliminate the number of Czechs working in Slovakia in a short time. Under dramatic circumstances, Měrka and his family were forced to leave Nitra and the territory of Slovakia.